Measurement of glottal cycle characteristics between children and adults: physiological variations - Patel, Rita R.; Dubrovskiy, Denis; Döllinger, Michael (Journal of Voice, 2014)
The aim of this study was to quantify phases of the vibratory cycle using measurements of glottal cycle quotients and glottal cycle derivatives, in typically developing prepubertal children and young adults with the use of high-speed digital imaging (HSDI).Vocal fold vibrations were recorded from 27 children (age range 5-9 years) and 35 adults (age range 21-45 years), with HSDI at 4000 frames per second for sustained phonation. Glottal area waveform measures of Open Quotient, Closing Quotient, Speed Index (SI), Rate Quotient, and Asymmetry Quotient (AsyQ) were computed. Glottal cycle derivatives of Amplitude Quotient (AQ) and Maximum Area Declination Rate (MADR) were also computed. Group differences (adult females, adult males, and children) were statistically investigated for mean and standard deviation values of the glottal cycle quotients and glottal cycle derivatives.Children exhibited higher values of SI and AsyQ and lower values of MADR compared with adult males. Children exhibited the highest mean value and lowest variability in AQ compared with adult males and females. Adult males showed lower values of SI, AsyQ, AQ, and higher values of MADR compared with adult females.Glottal cycle vibratory motion in children is functionally different compared with adult males and females, suggesting the need for development of children specific norms for both normal and disordered voice qualities.
EVALuna2:20184